How do drinking cultures change? – or do they?: A provisional model based on evidence of transitions in Denmark. (3rd July 2016) - Bloomfield, Kim; Karlsson, Thomas; Grittner, Ulrike
Abstract: Denmark, along with other industrialised nations, has experienced recent declines in alcohol consumption and other changes to its drinking culture. The point of departure for this study stems from growing evidence of changes in the Danish drinking culture. We have thus proposed a model to describe a society's drinking culture and have then applied it to the Danish case. We examine trends for several components of the model and focus roughly on a 10-year period from 2003 to 2013. The components include longitudinal survey data on consumption and alcohol‐related harm, registry data on morbidity and mortality, alcohol taxes and prices, physical availability, consumer purchasing power, demographic and structural changes, drinking norms and attitudes, alcohol advertising, as well as health education and promotion efforts. Although unable to conduct formal tests of drinking culture change, a review of our assembled data points in the direction of declining or stagnating consumption and increasing restrictiveness in attitudes, policies and regulations, thus suggesting the start of a shift in drinking practises and perceptions in Denmark. Such changes may also apply to other industrialised countries. Future research should examine longer periods, refine the model and its components, and if possible, conduct formal tests of change.